Revisiting influence of marketing effectiveness and environmental awareness on buying behaviour of green product: a SEM approach - Uthamaputhran, Logeswari; Ahmad, Fais; Jaganathan, Mathivannan; HoeChee Hee, Chee Hee (2016)
Environmental sustainability become a prominent and unending issue in the third world economic countries such as Malaysia. Although, “green” and “go green” concepts were emphasized by academicians and practitioners to explain the need to save the earth but environmental consciousness is remain at beginning stage. Therefore, the purpose of this study is to determine green buying behaviour among undergraduate students using environmental awareness or concern and marketing effectiveness as independent variables and intention as a mediator. Total 375 usable questionnaires were used for the purpose of analysis. Our findings support the influence of environmental awareness and marketing effectiveness on the intention and influence of intention on buying behaviour. Similarly, environmental awareness and marketing effectiveness mediated by intention on buying behaviour. The results of this study can be used by public and marketers to encourage pro-environmental behaviours. The recommendation, limitation and conclusion are then discussed at the end of the paper